Stunting Prevention Policy Among Pregnant Workers: Content Policy Analysis in Indonesia - Nurdiana, Astri; Ayuningtyas, Dumilah; Yuliatiningtyas, Solikhah; Nurhasana, Renny (Faculty of Nursing, Universitas Hasanuddin, 2025)
Aims: This study aims to analyze the extent to which national and regional stunting prevention policies in Indonesia, particularly in Karawang Regency, accommodate the needs of pregnant women working in industrial sectors. It examines whether current policy content effectively addresses occupational vulnerabilities and supports the first 1, 000 Days of Life initiative. Methods: A qualitative content analysis approach was employed using document analysis guided by the Ready, Extract, Analyze, and Distill (READ) method. Four policy documents were examined: Presidential Regulation No. 72 of 2021 and three regional policies in Karawang after 2021. Dunn’s Public Policy Analysis framework was used in this study. Results: The findings reveal seven themes of policy focus: government support, community empowerment, access to quality maternal healthcare, health human resource development, optimization of community health cadres, integration of data and information systems, and strengthening research and innovation. While pregnant women were identified as the target group, none of the policies explicitly included pregnant workers as a distinct subpopulation. The interventions mentioned in the policies are community-based and have a high risk of inaccessibility to industrial workers. Conclusion: Stunting prevention policies in the Karawang Regency have yet to operationalize an inclusive, context-sensitive approach for pregnant workers. The revised policies must align with international maternity protection standards and adopt workplace-based intervention models.